Facial Aesthetics: Babies Prefer Attractiveness to Symmetry. (November 2013) - Samuels, Curtis A; Butterworth, George; Roberts, Tony; Graupner, Lida; Hole, Graham
The visual preferences of human infants for faces that varied in their attractiveness and in their symmetry about the midline were explored. The aim was to establish whether infants' visual preference for attractive faces may be mediated by the vertical symmetry of the face. Chimeric faces, made from photographs of attractive and unattractive female faces, were produced by computer graphics. Babies looked longer at normal and at chimeric attractive faces than at normal and at chimeric unattractive faces. There were no developmental differences between the younger and older infants: all preferred to look at the attractive faces. Infants as young as 4 months showed similarity with adults in the 'aesthetic perception' of attractiveness and this preference was not based on the vertical symmetry of the face.